2003
DOI: 10.1289/ehp.6778
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in environmental health research.

Richard R Sharp

Abstract: Environmental health research encompasses a wide range of investigational topics, study designs, and empirical methodologies. As that arm of public health research concerned with understanding the health effects of the many environments in which humans live and work, the field is intimately connected with social concerns about environmental quality and disparities of power and privilege that place differential burdens upon members of underserved communities. Environmental health researchers thus engage many et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Studying industrial buyers of electronic products (the focus of this study) is particularly important in that the increasing awareness of environmental issues has stimulated concern about the disposal of products containing hazardous waste and the associated deleterious effects on the quality of the environment (Nnorom & Osibanjo, 2008). These ethical issues affect every type of business, enterprise, organization, and person (Sharp, 2003), thus making our research into the ethical brand concept both timely and crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Studying industrial buyers of electronic products (the focus of this study) is particularly important in that the increasing awareness of environmental issues has stimulated concern about the disposal of products containing hazardous waste and the associated deleterious effects on the quality of the environment (Nnorom & Osibanjo, 2008). These ethical issues affect every type of business, enterprise, organization, and person (Sharp, 2003), thus making our research into the ethical brand concept both timely and crucial.…”
Section: Introductionmentioning
confidence: 99%
“…These concerns have propelled research on genetic susceptibility and environmental conditions threatening the nation’s youth. Research approaches to confirmed, suspected, or as yet unidentified relationships between the environment and developmental disorders have included assessments of biologic mechanisms through which environmental toxicants affect children’s health, identification of populations that may be genetically susceptible to environmental diseases, and evaluation of interventions designed to mitigate harms associated with environmental hazards ( Sharp 2003 ).…”
mentioning
confidence: 99%
“…While an approach to decision-making is important, it should not be over looked that study design, selection of study population, and even what and where to study have ethical considerations (Sharp, 2003). The links between ethics and public health are being explored with the gowing recognition of the social and policy implications of this work (Callahan and Jennings, 2002;Kass, 2001).…”
Section: Ethical and Social Responsibilitymentioning
confidence: 99%